PKM Peran Mahasiswa Kampus Mengajar 7 dalam Meningkatkan Literasi dan Numerasi Peserta Didik di Sekolah Dasar Negeri 152977 Sarudik 1 - Permatasari, Dina Indah (Jurnal Masyarakat Indonesia (Jumas), 2025)
The Kampus Mengajar Program is part of the Merdeka Belajar policy which aims to involve students in supporting the learning process in elementary and junior high schools, especially those affected by the pandemic. This study aims to improve the literacy and numeracy skills of elementary school students through the implementation of the Kampus Mengajar Program. This activity is included in the type of community service with a descriptive qualitative approach. Data were collected through documentation of activities that were analyzed narratively. The results showed that the Kampus Mengajar program had a positive impact, such as improving basic reading and numeracy skills (addition, subtraction, multiplication, division), organizing play while learning activities, providing a reading room, and support in adapting technology and school administration. Students showed high enthusiasm and motivation to learn during the implementation of the program. Keywords: Kampus Mengajar, Literacy, Numeracy